Growth-related disappearance of the childhood relationship between height and blood pressure levels. (January 2014) - Fujita, Yuki; Kouda, Katsuyasu; Nakamura, Harunobu; Nishio, Nobuhiro; Takeuchi, Hiroichi; Iki, Masayuki
Abstract Context: Although there is a positive relationship between height and blood pressure (BP) levels in children, there are no reports regarding the association between height and BP levels in adolescents and adults. Objective: This study examined whether there is an association between height and BP levels in Japanese adolescents. Methods: The source population was all fifth (10 and 11-year-olds) and ninth graders (14 and 15-year-olds) who attended 11 elementary schools and five junior high schools in the Iwata area from 2002–2008. School-based screenings were conducted annually by the local government from April to June. Data obtained from health examinations were analysed, including anthropometric measurements and BP levels, for 11 780 children (98.7% of the source population). Results: Height showed significant positive relationships with systolic blood pressure (SBP) and diastolic blood pressure (DBP) in childhood and in adolescent males. In contrast, the relationship between height and SBP was significantly weaker in adolescent females than in childhood and there was no significant relationship between height and DBP in adolescent females. Conclusion: The relationship between height and SBP was attenuated by development in females and the relationship between height and DBP disappeared.